Peptide hydrogels — a tissue engineering strategy for the prevention of oesophageal strictures - Kumar, Deepak; Workman, Victoria; O'Brien, Marie Claire; McLaren, Jane S.; White, Lisa J.; Ragunath, Krish; Saiani, Alberto; Gough, Julie; Rose, Felicity R.A.J. (Wiley, 2017)
Endoscopic treatment of Barrett’s oesophagus often leads to further damage of healthy tissue causing fibrotic tissue formation termed as strictures. This study shows that synthetic, self-assembling peptide hydrogels (PeptiGelDesign) support the activity and function of primary oesophageal cells, leading to epithelialisation and stratification during in vitro 3D co-culture. Following buffering in culture media, oesophageal stromal fibroblasts (rOSFs) were incorporated into a library of peptide hydrogels, whereas oesophageal epithelial cells (mOECs) were seeded on the surface. Optimal hydrogels (PGD-AlphaProC and PGD-CGD2) supported mOEC viability (>95 %), typical cell morphology (cobblestone-like), a migration rate of 17.4 μm/hr and a migration distance of 364 μm, at 48 hours. Positive expression of typical epithelial markers (ZO-1 and cytokeratins) was witnessed detected using immunocytochemistry at day 3 in culture. Furthermore, optimal hydrogels were identified which supported rOSF viability (> 95%) with homogenous distribution when incorporated into the hydrogels and also promoted the secretion of collagen type I detected using ELISA, at day 7. 3D co-culture model using optimal hydrogels for both cell types supported a stratified epithelial layer (expressing involucrin and AE1/AE3 markers). Findings from this study could lead to the use of peptide hydrogels as a minimally invasive endoscopic therapy to manage oesophageal strictures.